Fenomena Pergeseran Makna dan Fungsi Tari Gundala-Gundala di Berastagi - Via Aurelia Br Brahmana; Muhammad Ihsan Syahaf Nasution; Christin Eva Febiola Simajuntak; Nadya Deswita (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2026)
This study examines the historical development, symbolic meanings, functions, and cultural transformation of the Gundala-Gundala Dance in Berastagi, a traditional performance of the Karo people rooted in the Sigurda-gurdi mythology and the Ndilo Wari Udan rain ritual. The research addresses the changing role of the dance amid social, cultural, and religious transformations while exploring how its cultural significance has been maintained. Employing Kuntowijoyo’s historical method, the study collected data through literature review, observation, documentation, and in-depth interviews. The findings reveal that the Gundala-Gundala Dance embodies spiritual, symbolic, and social values manifested through its movements, masks, costumes, and traditional music. Although its primary function has shifted from a sacred rain-invoking ritual to cultural performances, festivals, tourism, and official ceremonies, the dance continues to preserve the collective identity and cultural values of the Karo community. The novelty of this study lies in integrating historical analysis with cultural transformation to explain the continuity and adaptation of Gundala-Gundala as both ritual heritage and cultural performance. These findings contribute to the development of cultural communication and heritage studies while providing practical insights for safeguarding Karo cultural heritage amid contemporary social change.